FEATURES OF INTERACTION IN THE COMPANIES IN СONDITIONS OF DIGITALIZATION DEVELOPMENT - I. Groshev; A. Zheregelya (Вестник университета)
Digitalization in the modern world has an impact on all spheres of life. Interactions within the company are also changing. For the company to remain flexible, a special approach to workflows and communications is required. Digital tools allow build interaction in the company at a such level, when the maximum circle of people is involved in decision-making in direct contact with customers. The latter are full partners of the company. Hierarchical organizations are being replaced by self-governing systems and new concepts of organizational behavior.